Academic Performance and Technology Acceptance Model (TAM) Through a Flipped Classroom Experience: Training of Future Teachers of Primary Education. Issue 3 (2021) - Cabero-Almenara, Julio; Romero-Tena, Rosalía; Llorente-Cejudo, Carmen; Palacios-Rodríguez, Antonio
No abstract available